Analysis of factors influencing personal protective equipment use behavior among students in vocational high school engineering workshops - Renjistian Viga Vidariatma; Suherman Suherman; Triana Srisantyorini; Januar Ariyanto (Institute of Computer Science (IOCS), 2026)
Background: The behavior of using Personal Protective Equipment (PPE) among technical workshop students plays an important role in preventing workplace accidents and injury risks during practical activities. However, students’ compliance levels in using PPE vary and are influenced by various individual and environmental factors. Purpose: To analyze the factors influencing PPE usage behavior among students in the Technical Workshop of Vocational High School. Methods: This study used a quantitative approach with a cross-sectional design. The population consisted of 1,981 students, with a sample of 205 students selected using stratified random sampling. Data were collected using validated and reliable questionnaires, as well as primary and secondary data sources. The analyses conducted included univariate, bivariate, and multivariate analyses. Results: The results showed that 39.5% of students demonstrated compliant PPE usage behavior, while 60.5% were non-compliant. Bivariate analysis indicated significant relationships between attitude (p-value = 0.016; OR = 0.016) and motivation (p-value = 0.008; OR = 0.008) with PPE usage behavior. No significant relationship was found between knowledge (p-value = 0.644), PPE availability (p-value = 0.113), training (p-value = 0.537), supervision (p-value = 1.00), and peer influence (p-value = 0.570) with PPE usage behavior. Multivariate analysis showed that motivation (p-value = 0.006 < 0.05) was the most influential variable affecting PPE usage behavior among students in the workshop (OR = 2.381). Conclusion: Motivation is the dominant factor influencing PPE usage behavior among workshop students.